Serum keratin 19 (CYFRA21-1) links ductular reaction with portal hypertension and outcome of various advanced liver diseases - Karim Hamesch (BMC Medicine, 2020)
Abstract Background Keratins (Ks) represent tissue-specific proteins. K18 is produced in hepatocytes while K19, the most widely used ductular reaction (DR) marker, is found in cholangiocytes and hepatic progenitor cells. K18-based serum fragments are commonly used liver disease predictors, while K19-based serum fragments detected through CYFRA21-1 are established tumor but not liver disease markers yet. Since DR reflects the severity of the underlying liver disease, we systematically evaluated the usefulness of CYFRA21-1 in different liver disease severities and etiologies. Methods Hepatic expression of ductular keratins (K7/K19/K23) was analyzed in 57 patients with chronic liver disease (cohort i). Serum CYFRA21-1 levels were measured in 333 Austrians with advanced chronic liver disease (ACLD) of various etiologies undergoing hepatic venous pressure gradient (HVPG) measurement (cohort ii), 231 French patients with alcoholic cirrhosis (cohort iii), and 280 hospitalized Germans with decompensated cirrhosis of various etiologies (cohort iv). Results (i) Hepatic K19 levels were comparable among F0–F3 fibrosis stages, but increased in cirrhosis. Hepatic K19 mRNA strongly correlated with the levels of other DR-specific keratins. (ii) In ACLD, increased serum CYFRA21-1 associated with the presence of clinically significant portal hypertension (CSPH; HVPG ≥ 10 mmHg) (OR = 5.87 [2.95–11.68]) and mortality (HR = 3.02 [1.78–5.13]; median follow-up 22 months). (iii) In alcoholic cirrhosis, elevated serum CYFRA21-1 indicated increased risk of death/liver transplantation (HR = 2.59 [1.64–4.09]) and of HCC (HR = 1.74 [1.02–2.96]) over the long term (median follow-up 73 months). (iv) In decompensated cirrhosis, higher serum CYFRA21-1 predicted 90-day mortality (HR = 2.97 [1.92–4.60]) with a moderate accuracy (AUROC 0.64), independently from established prognostic scores. Conclusions Hepatic K19 mRNA and serum CYFRA21-1 levels rise in cirrhosis. Increased CYFRA21-1 levels associate with the presence of CSPH and reliably indicate mortality in the short and long term independently of conventional liver biochemistry markers or scoring systems. Hence, the widely available serum CYFRA21-1 constitutes a novel, DR-related marker with prognostic implications in patients with different settings of advanced liver disease.